Komi reindeer herding: mobility and land use in a changing natural and social environment - Dwyer, Mark James (University of Cambridge, 2006)
The file processed with OCR is smaller and allows cutting and pasting (though this may contain errors). The file without OCR is much larger and does not allow cutting and pasting but the visual quality is superior. Nomadic pastoralism is a form of animal husbandry characterised by movement. Herders and their animals move across the tundra and taiga displaying a curious dichotomous relationship of control by and response to each other. This field based research - carried out among Komi nomadic reindeer herders of the Russian far north - examines how Komi pastoral nomads choose a particular time, route and length of migration. This was explored by using anthropological as well as ecological methods to (i) identify how social and political change and environmental variability influence the reindeers’ and herders’ movements alike and (ii) examine how nomadic movements occur in relation to nonecological and ecological factors. It was found that there were essentially two types of human / animal movements; individual movements (made by the duty herder and his herd) and collective movements (made by the brigade). Both types of movement, in time and space, were fundamentally dependent upon herding skill and knowledge, and herd control: (a) the duty herder’s ability to maintain herd cohesion and (b) the general aim of preventing harm befalling the herd (by avoiding dangerous terrain). The duty herder’s selection of pastures was, therefore, made mainly according to where reindeer were the easiest to control. It was also found that individual movements could best be understood as emanating from the interplay between reindeer behaviour and the duty herder’s actions. This interplay is best described as being the duty herder’s skilful perception of and response to ethological changes, as advocated by Tim Ingold. Its main principle is based on the duty herder’s maintenance of herd cohesion, within a restricted territory, which has minimal impact upon reindeer behaviour, and which is achieved through skilful manoeuvring. ...